Regional differences in mortality in Greece (1984-2004): The case of Thrace - Zilidis Christos; Polyzou Konstantina; Rachiotis George; Papastergiou Panagiotis; Hadjichristodoulou Christos (BMC, 2008)
Abstract Background Mortality differences at national level can generate hypothesis on possible causal association that could be further investigated. The aim of the present study was to identify regions with high mortality rates in Greece. Methods Age adjusted specific mortality rates by gender were calculated in each of the 10 regions of Greece during the period 1984-2004. Moreover standardized mortality rates (SMR) were also calculated by using population census data of years 1981, 1991, 2001. The mortality rates were examined in relation to GDP per capita, the ratio of hospital beds, and doctors per population for each region. Results During the study period, the region of Thrace recorded the highest mortality rate at almost all age groups in both sexes among the ten Greek regions. Thrace had one of the lowest GDP per capita (11 123 Euro) and recorded low ratios of Physicians (284) per 100 000 inhabitants in comparison to the national ratios. Moreover the ratio of hospital beds per population was in Thrace very low (268/100 000) in comparison to the national ratio (470/100 000). Thrace is the Greek region with the highest percentage of Muslim population (33%). Multivariate analysis revealed that GDP and doctors/100000 inhabitants were associated with increased mortality in Thrace. Conclusion Thrace is the region with the highest mortality rate in Greece. Further research is needed to assess the contribution of each possible risk factor to the increased mortality rate of Thrace which could have important public health implications.